Engulfment-regulated proteolysis of SpoIIQ: evidence that dual checkpoints control sigma activity - Jiang, Xin; Rubio, Aileen; Chiba, Shinobu; Pogliano, Kit (Molecular microbiology, 2005)
During Bacillus subtilis sporulation, the engulfment checkpoint is thought to directly regulate late forespore transcription but to indirectly regulate late mother cell transcription, via the sigmaG-produced protease SpoIVB. We here demonstrate that SpoIIQ is subject to sigmaG-independent, but engulfment-dependent, proteolysis that depends on SpoIVB. Thus, SpoIVB produced before engulfment supports some SpoIVB-dependent events, suggesting that its activity or access to substrates must be regulated by engulfment. Furthermore, a mutation (bofA) that allows sigmaK to be active without sigmaG does not allow sigmaK activity in engulfment mutants, although the pro-sigmaK processing enzyme (SpoIVFB) is localized to the septum in engulfment mutants, suggesting that engulfment comprises a second checkpoint for sigmaK Finally, we find that SpoIIQ and another protein required for sigmaG activity (SpoIIIAH), which directly interact and assemble helical structures around the forespore, recruit the sigmaK-processing enzyme SpoIVFB to the forespore and these structures. We suggest that these foci serve a synapse-like role, allowing engulfment to simultaneously control both sigmaG and sigmaK, and integrating multiple checkpoints and signalling pathways.